2021
DOI: 10.3389/fimmu.2021.694720
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Betaine Mitigates Hepatic Steatosis and Inflammation Induced by a High-Fat-Diet by Modulating the Sirt1/Srebp-1/Pparɑ Pathway in Juvenile Black Seabream (Acanthopagrus schlegelii)

Abstract: The present study aimed to elucidate the mechanism of dietary betaine, as a lipid-lowering substance, on the regulation of lipid metabolism and inflammation in juvenile black seabream (Acanthopagrus schlegelii) fed a high fat diet. An 8-week feeding trial was conducted in black seabream with an initial weight of 8.39 ± 0.01g fed four isonitrogenous diets including Control, medium-fat diet (11%); HFD, high-fat diet (17%); and HFD supplemented with two levels (10 and 20 g/kg) of betaine, HFD+B1 and HFD+B2, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…A previous study has shown that salinity stress could limit the immune system function of fish, leading to the decline of immune function ( 64 ). Nuclear factor kappa B (Nf-κb) is a vital nuclear transcription factor, when NF-κB is activated, it transfers into the nucleus and promotes the expression of pro-inflammatory cytokines, including tnf- α and il-1 β ( 56 , 65 ). Besides, Tnf-α is processed as a membrane-bound protein from which the soluble active factor is cleaved by using the enzyme Tnf-α converting enzyme and Il-1 β is one of the important pro-inflammatory cytokines produced by phagocytes ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that salinity stress could limit the immune system function of fish, leading to the decline of immune function ( 64 ). Nuclear factor kappa B (Nf-κb) is a vital nuclear transcription factor, when NF-κB is activated, it transfers into the nucleus and promotes the expression of pro-inflammatory cytokines, including tnf- α and il-1 β ( 56 , 65 ). Besides, Tnf-α is processed as a membrane-bound protein from which the soluble active factor is cleaved by using the enzyme Tnf-α converting enzyme and Il-1 β is one of the important pro-inflammatory cytokines produced by phagocytes ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…The immune response enhancement herein could be attributed to the increasing WBC counts by Bet supplementation, as was pointed out in our previous study (Abeer et al, 2015). In a similar context, 8 weeks of high‐fat diet feeding with two levels of Bet (10 and 20 g/kg) attenuated the inflammatory responses of juvenile black seabream ( Acanthopagrus schlegelii ) (Jin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Betaine, a food-derived substance [ 24 ], serves as a methyl donor for DNA methylation [ 25 , 26 , 27 ]. Betaine levels in the blood were inversely associated with the severity of NAFLD in human [ 28 ], and many studies suggest a preventive role of betaine in NAFLD [ 29 , 30 ], type 2 diabetes [ 31 ] and inflammation [ 32 ]. Nevertheless, only two studies reported the efficacy of betaine in the treatment of rat NAFLD models [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%